INTEGRATING CRITICAL LITERACY AND MULTIMODAL PEDAGOGY IN ENGLISH LANGUAGE EDUCATION - Jusak Patty (Program Studi Pendidikan Bahasa Inggris, 2025)
English language learners encounter texts that extend beyond alphabetic modes, navigating advertisements, social media posts, and digital platforms where meaning emerges from linguistic, visual, audio, gestural, and spatial resources operating simultaneously. This narrative review synthesizes contemporary research examining the intersection of critical literacy and multimodal pedagogy in English language education, with particular attention to Asian EFL contexts. The review analyzed empirical studies organized thematically to examine how theoretical frameworks inform pedagogical practice, how implementations address contextual challenges, and how teacher education prepares educators for multimodal critical literacy instruction. Findings reveal that project-based, problem-based, digital storytelling, and genre-based approaches effectively develop critical multimodal literacy when combined with explicit metalinguistic instruction and appropriate scaffolding. Implementation challenges in Asian EFL contexts include language proficiency requirements, cultural considerations for critical engagement, gaps in teacher preparedness, and disparities in resource access. Technology integration studies demonstrate that digital platforms and AI tools expand possibilities for multimodal composition while requiring critical digital literacy frameworks. Assessment approaches have evolved from product-focused to process- and genre-based models that acknowledge the complexity of multimodality. Teacher education implications emphasize the need for professional development focused on semiotic awareness, multimodal pedagogical content knowledge, and critical orientations, with localized adaptations tailored to specific educational contexts. These insights underscore the importance of context-responsive pedagogy and sustained teacher learning for effectively implementing multimodal critical literacy across diverse EFL classrooms.